Research Progress in Microbe-Gut-Liver Axis and Alcoholic Liver Disease and Nutritional Interventions for It - ZHENG Hongxing, JI Le, QI Shanshan (Shipin Kexue)
Alcoholic liver disease (ALD) is the most common type of chronic liver disease worldwide, manifesting as fatty liver at the early stage, and then evolving into steatohepatitis. ALD can further develop into liver fibrosis and cirrhosis with increasing alcohol consumption. The gut-liver axis refers to the bidirectional interaction between the gut and its microbiota and the liver, established through the portal vein and the biliary tract. Alcohol can disrupt this bidirectional effect, leading to the disturbance of the gut microbiota and the translocation of pathogens to the liver, and finally causing liver damage. In this article, the mechanism of action of the gut-liver axis in mediating the occurrence and development of ALD and the nutritional interventions for ALD are reviewed mainly from the following aspects: the intestinal barrier, intestinal microbial composition, and intestinal microbial metabolites. Particular focus is placed on the intervention of targeted phages in the gut microbiota and the role of trimethylamine, cytolysin and candidin in ALD. It is our hope that this review will provide basic data for the discovery of anti-ALD substances targeting the gut-liver axis and for the development of new nutritional interventions and functional foods.